Traffic congestions in Dhaka and socio-economic development in Bangladesh: some micro and macro-level connections - Ahmed, Ansar (© 2017 Bangladesh Development Initiative & The University Press Limited., 2017)
This book chapter was published in the Development Issues of Bangladesh -III: Human Development and Quality of Life [© 2007 Bangladesh Development Initiative & The University Press Limited ] and the publisher details available at : http://www.uplbooks.com/book/development-issues-bangladesh-iii-human-development-and-quality-life